Experience of family support coordinators for the Child Cancer Foundation in the development and use of the Wellbeing Check-in booklet distress screening tool : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Albany, Aotearoa/New Zealand - Prasad, Nandini (Massey University, 2022)
A paediatric cancer diagnosis presents many psychosocial complications for the patient and the family/whānau involved. Therefore, implementing systems that asses for early distress screening and the adverse sequelae cancer presents can reduce long-term psychosocial problems and, by virtue, reduce pressures on secondary health systems in Aotearoa, New Zealand. However, despite the wealth of literature supporting distress screening as evidence-based practice, there is still a need for support services to implement distress screening, particularly within paediatric cancer care successfully, and specifically care that extends beyond the patient towards the family/whānau. Hence, in the second part of the Distress Screening Project, working collaboratively with the Child Cancer Foundation and Family Support Coordinators (FSC), this research project aimed to understand the experiences of FSCs in the use of the Wellbeing Check-in booklet distress screening tool. Through using the qualitative methodology of Interpretative Phenomenological Analysis (IPA), a total of five FSCs were interviewed. The results revealed six major themes with subsequent subthemes: Flexibility of the Wellbeing check-in booklet distress screening tool; Providing a framework to conversations; Facilitating conversations; Parent/Caregiver focussed outcomes; Overcoming barriers; and Benefits and suggestions. The results indicate that the Wellbeing Check-in Booklet Distress Screening Tool is an effective and holistic distress screening tool in assessing the wellbeing of families/whānau of a child cancer patient within paediatric oncology. Furthermore, it was a valuable tool for the FSCs to use in their role and was well received by the parents and caregivers in their care. Future research should acknowledge the strengths of the booklet identified through this study and review the barriers discovered for future research. The results of this study have implications for the future of paediatric psychosocial oncological care in Aotearoa, New Zealand.
Keywords: 520304 Health psychology